2005
DOI: 10.1096/fj.04-2201com
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the human atrial myosin light chain 1 promoter by Ca2+‐calmodulin‐dependent signaling pathways

Abstract: We investigated expression regulation of the human atrial myosin light chain 1 (hALC-1) gene using a cardiomyocyte H9c2 cell line stably transfected with a construct consisting of the human ALC-1 promoter cloned in front of the luciferase gene (H9c2T1). H9c2T1 cells were stimulated with vasopressin, which is known to induce cardiomyocyte hypertrophy and to activate a panel of signaling pathways. Those pathways involved in hALC-1 promoter activity regulation were dissected by using pharmacological inhibitor sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…PP2A levels are increased in differentiated H9C2 cells, and PP2A has been shown to dephosphorylate CaMKIV, inhibiting its activity (37,39). To determine whether HDAC5 nuclear localization in differentiated cells is dependent on PP2A, cells were treated with the PP2A inhibitor okadaic acid for 2 h after the differentiation process.…”
Section: Inhibition Of Camkiv/pkd Results In Change In Yy1 Function Imentioning
confidence: 99%
See 2 more Smart Citations
“…PP2A levels are increased in differentiated H9C2 cells, and PP2A has been shown to dephosphorylate CaMKIV, inhibiting its activity (37,39). To determine whether HDAC5 nuclear localization in differentiated cells is dependent on PP2A, cells were treated with the PP2A inhibitor okadaic acid for 2 h after the differentiation process.…”
Section: Inhibition Of Camkiv/pkd Results In Change In Yy1 Function Imentioning
confidence: 99%
“…We also showed that PP2A is involved in HDAC5 nuclear localization in differentiated cells. PP2A levels are increased in differentiated cells (11), and PP2A promotes CaMKIV dephosphorylation (36,37). We cannot determine whether HDAC5 nuclear localization in differentiated cells is a direct consequence of PP2A dephosphorylation of HDAC5 or whether it is a consequence of CaMKIV inactivation.…”
Section: Yy1 Functional Domainsmentioning
confidence: 96%
See 1 more Smart Citation
“…The dominant role of the Ca 2ϩ -calmodulin-dependent signaling pathway in the regulation of human ELC a expression was shown by Woischwill et al (111). The expression of ELC a in compartments other than the atrium has been associated with a diseased and/or hypertrophied heart (for review see Refs 54 and 65).…”
Section: Atrial Elcmentioning
confidence: 98%
“…A proposed mechanism for improved Ca 2+ sensitivity has been that troponins T [22] and I [23] undergo a shift in the isoforms expressed and that atrial myosin light chain 1 increases expression levels [24]. It has also been shown that CaMKII can act to mediate troponin I function [8] and the promoter-region of the atrial myosin light chain-1 gene [25]. It now appears that CaMKII may be able to acutely induce a shift in the myofilament sensitivity to Ca 2+ to a more energetically favorable state after exercise training, although other studies have suggested that PKA mediates Ca 2+ sensitivity [26].…”
Section: Myofilament Ca 2+ Sensitivitymentioning
confidence: 99%